Studi Living Law Tradisi Malem Songo dalam Menegosiasikan Pantangan dan Memperkuat Kohesi Sosial - Gandhung Fajar Panjalu (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2025)
This study aims to analyze the dual function of this tradition as a mechanism for annulling Javanese marital taboos and an instrument for strengthening social cohesion in Bojonegoro society, employing an anthropological-sociological approach. The research utilized a qualitative case study method through participant observation, in-depth interviews with 14 informants, and document studies. Data were analyzed thematically using an interdisciplinary approach, integrating perspectives from Ehrlich's Legal Anthropology, Merton's Structural Functionalism, and Durkheim's Social Solidarity theory. The findings reveal that Malem Songo functions as a living law, offering a cultural solution for couples facing customary taboos (such as Jilu and incompatible weton calculations), while simultaneously serving as a strategic moment to strengthen bonding and bridging social capital through homecoming (mudik) and mass weddings. It is concluded that this tradition is a self-reinforcing socio-cultural system achieved through the dialectic of its annulment and solidarity functions. The importance of education that balances tradition preservation with a rational understanding of customary values is suggested.